Corruption and New Product Innovation: Examining Firms’ Ethical Dilemmas in Transition Economies - Xie, Xuemei (Journal of business ethics, 2019)
Corruption as a non-market strategy for firms has gained increasing attention in the field of strategy management. However, the effect of corruption on innovation is unclear, especially in the context of transition economies. Using institutional theory, we examine the relationship between corruption and new product innovation and identify the contextual conditions of the relationship. Using the World Bank Enterprise Survey data from China, our empirical results show that corruption has a positive effect on firms’ new product innovation. Moreover, we find that policy instability and competitive threats from the informal sector positively moderate the relationship between corruption and new product innovation. Using post hoc analysis, we find that the potentially positive effect of corruption on new product innovation is the consequence of inherent institutional weaknesses in transition economies; as the level of institutional development increases, the effect of corruption on firms’ new product innovation will gradually decrease. Overall, our findings provide new insights into understanding corrupt behaviors in transition economies and present managerial implications for firms’ ethical dilemmas in a transition economy context. We argue that the key to overcoming these ethical dilemmas lies in promoting pro-market institutional reform to reduce the potential benefits of corruption.